A most dangerous voyage : - Green, Jeannine (University of Alberta Libraries, 2008)
Arctic exploration has long captured the interest and imagination of explorers, nations, and the public. For more than 400 years, European explorers were lured to the Arctic to try to discover a commercial trading route to the Far East, where gold, spices, silk, and other valuable goods were readily available. Expeditions failed to locate the elusive Northwest Passage because virtually nothing was known about the Arctic Archipelago. Early mariners believed that Arctic waters were not frozen for the entire year, but of course it was a false hope that summer months offered safe passage. The cold was always extreme, and tiny wooden vessels were easily crushed against soaring icebergs and ice-choked channels. This exhibit catalogue, published to accompany a 2008 exhibit at the University of Alberta's Bruce Peel Special Collections Library, showcases a selection of books and maps documenting this perilous endeavour.